ANALISIS PERBANDINGAN MUTU BETON DENGAN MENGGUNAKAN BERBAGAI CARA PENGADUKAN (READY MIX, MOLEN DAN MANUAL) - Rahelina Ginting; Winarko Malau (Jurnal Darma Agung, 2020)
Concrete work is widely used in construction projects now. To get a good quality concrete depends very much on the quality of the constituent materials, namely cement, water, fine aggregate, coarse aggregate, and also the process of working or stirring. In this research, 27 MPa concrete compressive strength will be investigated with various stirring methods (Manual Mix, Molen Mix and Ready Mix). These three methods of stirring certainly have their respective uses in the process, usually Manual, Molen and Ready Mix are used depending on the conditions of the project being worked on. From this test, results are obtained by means of manual stirring, Molen stirring and Ready Mix with compressive strength average: (266,467 kg / cm2) (278,368 kg / cm2) (284,595 kg / cm2). The results of the study stated that the research carried out fulfilled the estimation target 'c = 27 Mpa.